Mastoid obliteration and external auditory canal reconstruction using 3D printed bioactive glass S53P4 /polycaprolactone scaffold loaded with bone morphogenetic protein-2: A simulation clinical study in rabbits - Yu, Fenghui; Fan, Xiaoxia; Wu, Hongxia; Ou, Yangxi; Zhao, Xuxu; Chen, Tao; Qian, Yi; Kang, Houyong (Regenerative therapy, 2022)
The lack of good prosthetic materials and objective standards has limited the promotion of mastoid obliteration and external auditory canal reconstruction, and the quality of the surgery varies. In this study, bioactive glass S53P4 (S53P4), the most popular artificial prosthetic material, was modified and combined with polycaprolactone (PCL) and bone morphogenetic protein-2 (BMP-2) to produce an individualized biological scaffold using 3D printing technology to explore a better material and method for mastoid obliteration and external auditory canal reconstruction. 3D-printed S53P4/PCL scaffolds were fabricated from 3D reconstruction data of bone defect areas in New Zealand rabbits simulating “Canal Wall Down Mastoidectomy”. The water absorption, swelling rate, porosity, and Young's modulus of the scaffold were measured, and the morphology and pore size of the scaffold were observed using scanning electron microscopy. The cytotoxicity of the S53P4/PCL scaffolds was detected using the CCK8 assay, and the in vitro antibacterial activity of the S53P4/PCL scaffolds was detected using the inhibition circle method. The BMP-2-loaded S53P4/PCL scaffolds were prepared using the drop-in lyophilization method and implanted into animal models. The biocompatibility, osteogenic activity, and external auditory canal repair of the scaffolds were observed using endoscopy, micro-CT, and histological examination. The S53P4/PCL scaffold was highly compatible with the defective area of the animal model, and its physicochemical properties met the requirements of bone tissue engineering. In vitro experiments showed that the S53P4/PCL scaffold was non-cytotoxic and exhibited better antibacterial activity than the same volume of the S53P4 powder. In vivo experiments showed that the S53P4/PCL scaffold had good biocompatibility and osteogenic activity, and could effectively repair bone defects and reconstruct the normal morphology of the external auditory canal in animal models. Furthermore, its osteogenic activity and repair ability were significantly improved after loading with BMP-2. The 3D printed S53P4/PCL scaffold has great potential for clinical mastoid obliteration and external auditory canal reconstruction. •Canal wall-down mastoidectomy was simulated to construct an animal model.•S53P4/PCL scaffold could reconstruct the normal shape of the external auditory canal.•The scaffold had better antibacterial activity than the same volume of S53P4 powder.•Repair ability of S53P4/PCL scaffolds significantly improved after loading with BMP-2.